Self-Structured Breast Cancer Awareness among Female Adolescent - Rahayu Dewi Pangestuti; Ni Ketut Alit Armini; Lingga Curnia Dewi (Universitas Airlangga, 2021)
Introduction:The incidence of breast cancer has increased every year, mostly in developing countries. However, breast cancer awareness in women is still insufficient. A woman must be aware of breast cancer disease earlier. This study aimed to describe breast cancer awareness in female adolescents. Methods: The research design was used descriptive-analytic. The study population consisted of female adolescents in 10th-11th grade at Vocational High School in Surabaya, East Java, Indonesia. The sample was taken using stratified random sampling. There are 206 female adolescents aged 15-18 years old who participated in this study. Data collected using a self-structured breast cancer awareness questionnaire arranged by Breast Cancer Awareness Measurement (BCAM) guideline. The questionnaire consisted of breast cancer knowledge (disease, signs and symptoms, risk factors), perception, and BSE. The statistical analysis was using distribution frequency. Results: The result presented that the majority of female adolescents had high awareness (67,5%). The maximum score was knowledge of disease (3.28 ± 0.54) (table 3). The minimum score was risk factors knowledge (1.95 ± 0.69) and BSE (1.81 ± 0.78). Conclusion: The respondents have good knowledge of breast cancer disease yet understanding of risk factors is low. It is necessary to do counseling programs in school, particularly women's reproductive health and breast self-examination (BSE) due to improve knowledge of risk factors in female adolescents.